EFEKTIVITAS KERJA PEGAWAI DINAS PEMBERDAYAAN MASYARAKAT DAN DESA KABUPATE SUMEDANG - Akadun; Eneng Ida Mursyidah; Kosman Data (LPPM UNSAP & FISIP UNSAP, 2019)
This research aims to find out the Effectiveness of Employee Work in the Community Empowerment Office and Sumedang Regency Village, what inhibitory factors are found in the implementation of the effectiveness of employee work in the Community Empowerment Office and Sumedang Regency Village and what efforts are made to overcome inhibiting factors in the implementation of Employee Work Effectiveness in the Community Empowerment Office and Sumedang Regency Village. The method used in this study is a qualitative method, using the purposive sampling method. With research informants as many as 4 people, namely Kasubag General Assets and Staffing, Head of Institutional Affairs, Head of Community Economic Empowerment, and Head of Village Government. The data collection techniques used are literature studies, field studies (observations, interviews, and documentation). While the processing procedures in this study, namely data reduction, data display, data conclusion drawing / verification and triangulation. The final results of this study concluded that on the aspect of quality of work is quite good because it already has responsibility. And in the quantity aspect as a whole has reached the target and target and in the aspect of timeliness the employees are quite disciplined. Inhibiting factors found in the effectiveness of employee work in the Community and Village Empowerment office are aspects of adaptability, aspects of work performance, and aspects of job satisfaction. Efforts are made to overcome inhibiting factors in the effectiveness of employee work, namely by evaluating, including employees in education and training, providing motivation and holding family gatherings.